9^3x+4×корень из 3=27^x-1÷корень из 3

И1111111111111111 И1111111111111111    2   03.01.2022 14:52    1

Ответы
00012333334 00012333334  03.01.2022 15:00

х = - 4

Объяснение:

{9}^{3x + 4} \times \sqrt{3} = \frac{ {27}^{x - 1} }{ \sqrt{3} } | \times \sqrt{3} \\ {( {3}^{2}) }^{3x + 4} \times {( \sqrt{3})}^{2} = {( {3}^{3})}^{x - 1} \\ {3}^{2 \times (3x + 4)} \times {3}^{1} = {3}^{3 \times (x - 1)} \\ {3}^{6x + 9} = {3}^{3x - 3}

- простейшее показательное уравнение,

6х+9=3х-3

3х=-12

х=-4

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра